Design and Research of Urban Video Surveillance System - Peng He; Tianzhong Guo; Jingran An (Institute of Advanced Engineering and Science, 2014)
This paper aimed to design and realized Qiqihar urban video surveillance system and use advanced design solutions to improve the traditional city video surveillance system based on EPON technology. Hierarchical design was proposed and a detailed analysis of each design was given. The system not only has expanded capabilities in the structure, but also has integrated application capabilities in the business, including image transmission, remote monitoring, remote centralized digital image data storage, remote real-time on-demand playback (stored data image). The result shows that the system can completely solve the digitization of the monitoring system and the process of networking bottlenecks. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.3631